SINTESA NANOFIBER TITANIUM DIOKSIDA (TiO2) ANATASE MENGGUNAKAN METODE ELECTROSPINNING - Hendri Widiyandari; Agus Purwanto (Reaktor, 2015)
SYNTHESIS OF ANATASE TITANIUM DIOXIDE (TiO2) NANOFIBER BY ELECTROSPINNING METHOD. This research reported the synthesis of nanofiber anatase titanium dioxide (TiO2) using electrospinning. To produce nanofiber, the precursor solution was passed through a capillary of syringes given a positive DC voltage of 13 kV and then as-prepared nanofiber annealed at temperature of 500°C for 1 hour. The annealed samples were then analyzed using a scanning electron microscope (SEM) and x-ray diffractometer (XRD). In this study, the effect of changes in the flow rate of the precursor solution and the weight of raw material of titanium tetraisopropoxide (TTIP) to the crystallinity and morphology of the sample were systematically investigated. This research resulted that the TiO2 nanofiber have a mixed phase between anatase and rutile. The amount of rutile TiO2 could be reduced by increasing the flow rate of precursor solution. The optimum flow rate to obtain the pure anatase TiO2 was adjusted at 2.0 mL/h. In addition. TTIP weight affected the morphology of nanofiber which by increasing the amount of TTIP resulted morphological change to become more dense and uniform in shape and size. Keywords: anatase; electrospinning; nanofiber; rutile; titania Abstrak Pada penelitian ini telah berhasil dibuat nanofiber titanium dioksida (TiO2) anatase dengan menggunakan metode electrospinning. Nanofiber TiO2 dihasilkan dengan cara melewatkan larutan prekursor pada jarum suntik yang diberi tegangan DC positif 13 kV pada ujungnya. Fiber hasil spinning kemudian dikalsinasi pada suhu 500°C selama 1 jam. Sampel yang telah dikalsinasi kemudian dianalisis menggunakan scanning electron microscope (SEM) dan x-ray diffractometer (XRD). Pada penelitian ini pengaruh dari perubahan laju aliran larutan prekursor dan berat material baku titanium tetraisopropoxide (TTIP) terhadap sifat kristal dan morfologi sampel dikaji secara sistematis.  Dari penelitian ini diperoleh bahwa TiO2 yang dihasilkan memiliki fase campuran antara anatase dan rutile, namun dengan menaikkan laju aliran prekursor mampu menurunkan jumlah fase rutilenya sehingga pada laju aliran 2,0 mL/h diperoleh nanofiber TiO2 dengan fase anatase murni. Berat TTIP sangat mempengaruhi morfologi nanofiber yang diperoleh dimana dengan menaikkan jumlah TTIP morfologi fiber mangalami perubahan menjadi lebih padat (dense) dan lebih seragam baik bentuk dan ukurannya. Kata kunci: anatase; electrospinning; nanofiber; rutile; titania